2015
DOI: 10.1080/13102818.2015.1102612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2100 MHz mobile phone radiation on healing of mandibular fractures: an experimental study in rabbits

Abstract: Fractures in the maxillofacial region are among the most frequent incidences in patients exposed to trauma. The aim of this study was to evaluate the effect of 2100 MHz electromagnetic radiation on the healing of mandibular fractures in rabbits. The study was carried out on 12 mature male New Zealand rabbits. After producing a left mandibular osteotomy, the fracture was repaired by using a plate screw. The rabbits were divided into two groups À control and experimental. The experimental group was exposed for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, it was found that exposure to RF field significantly slowed bone resorption and improved bone mineral density (BMD) in the treatment of osteoporosis [Jayanand et al, 2003]. In addition, it was reported that 2100 MHz RF field significantly increased energy absorption capacity and positively affected fracture healing in rabbits [Durgun et al, 2016]. However, this report conflicted with Aslan et al's [2013Aslan et al's [ , 2014 findings; they found that RF at 900 MHz of frequency emitted from cellular phones had an adverse effect on bone fracture healing in a rat tibia model, and RF at 1800 MHz frequency emitted from cellular phones had no effect on bone fracture healing in rats.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that exposure to RF field significantly slowed bone resorption and improved bone mineral density (BMD) in the treatment of osteoporosis [Jayanand et al, 2003]. In addition, it was reported that 2100 MHz RF field significantly increased energy absorption capacity and positively affected fracture healing in rabbits [Durgun et al, 2016]. However, this report conflicted with Aslan et al's [2013Aslan et al's [ , 2014 findings; they found that RF at 900 MHz of frequency emitted from cellular phones had an adverse effect on bone fracture healing in a rat tibia model, and RF at 1800 MHz frequency emitted from cellular phones had no effect on bone fracture healing in rats.…”
Section: Introductionmentioning
confidence: 99%